2019
DOI: 10.1101/712190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Minor QTLs mining through the combination of GWAS and machine learning feature selection

Abstract: 2 Introduction: Minor QTLs mining has a very important role in genomic selection, pathway analysis and 3 trait development in agricultural and biological research. Since most individual loci contribute little to 4 complex trait variations, it remains a challenge for traditional statistical methods to identify minor QTLs 5 with subtle phenotypic effects. Here we applied a new framework which combined the GWAS analysis 6 and machine learning feature selection to explore new ways for the study of minor QTLs minin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(1 reference statement)
3
9
0
Order By: Relevance
“…Thus, it is possible that this marker is linked to Sspon.02G0027920-1A, the S. spontaneum gene syntenic to the auxin-binding protein gene at Scmv2 (Ding et al, 2012). This is an indication of the potential suitability of FS methodologies for the identification of QTLs, which is supported by other studies in which researchers analyzed traits controlled by many loci (Zhou et al, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…Thus, it is possible that this marker is linked to Sspon.02G0027920-1A, the S. spontaneum gene syntenic to the auxin-binding protein gene at Scmv2 (Ding et al, 2012). This is an indication of the potential suitability of FS methodologies for the identification of QTLs, which is supported by other studies in which researchers analyzed traits controlled by many loci (Zhou et al, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…Unlike these traditional statistical models, machine learning methods do not require these prior assumptions about the genetic architecture of traits and have been applied in GWAS in humans [30] as well as in livestock [27,95]. Especially, Romagnoni et al [30] and Huang et al [24] showed that machine learning based algorithms provide promising prediction power to assess genotype-phenotype associations. In particular, the Random Forests (RF) algorithm has been successfully applied for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these limitations of GWAS, application of Bayesian frameworks as well as machine learning algorithms have gained importance in the last decade [21][22][23][24][25]. Their comparative performance has been evaluated for a variety of traits with different genetic architectures (see the reviews [13,26,27]).…”
Section: Introductionmentioning
confidence: 99%
“…To select SNPs that were significantly associated with SRKN resistance, a Partial Least Square (PLS) ( Wold, 1966 ) model was fitted using the 4,974 SNPs as predictors and the number of galls in the root as responses. PLS models have the advantage to reduce the variability and instability of estimated responses caused by multicollinearity among predictors ( Zhou et al, 2019 ; James et al, 2021 ). Additionally, PLS creates linear combinations (known as components) of the original predictor variables (the SNPs) to explain the observed variability in the responses (the galling response).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, the applications of ML-based GWAS need to be consistently validated with significant associations that make both biological and statistical sense ( Nicholls et al, 2020 ). To the best of our knowledge, ML-based GWAS has been applied in soybean to identify significant marker-trait associations using SVM ( Yoosefzadeh-Najafabadi et al, 2021a , b ), RF ( Zhou et al, 2019 ; Xavier and Rainey, 2020 ; Yoosefzadeh-Najafabadi et al, 2021b ), and Deep Convolutional Neural Network (CNN) ( Liu et al, 2019 ), of which none was applied on soybean resistance to SRKN. Therefore, the objective of this study was to conduct ML-GWAS utilizing 717 diverse breeding lines derived from 330 unique bi-parental populations with two different algorithms (SVM and RF) to unveil novel regions of the soybean genome regulating the resistance to SRKN (reported as the development of galls in the roots) and contribute to developing enhanced and more durable SRKN resistance.…”
Section: Introductionmentioning
confidence: 99%